A safe and simple method for axIABP placement using a left axillary–radial technique. Issue 2 (26th September 2020) - Maatman, Benjamin; Rios‐Meza, Hugo; Guglin, Maya; Revtyak, George
Abstract: In patients with severe heart failure, a percutaneous axillary intraaortic balloon pump (axIABP) may permit ambulation while awaiting destination therapy. Traditionally, an "axillary–femoral" approach has been used with femoral access for axillary angiography during insertion. We describe an "axillary–radial" technique for axIABP insertion and removal using the left radial artery.